Growth and maintenance costs of leaves and roots in two populations of Quercus ilex native to distinct substrates - Laureano, Raquel G.; García-Nogales, Ana; Seco, José I.; Rodríguez, Jesús G. P.; Linares, Juan C.; Martínez, Feliciano; Merino, José (Plant and Soil, 2012)
Aims This work tests the hypothesis that growth and maintenance costs of plant organs are higher in more stressful soils. Methods Two populations of Quercus ilex L were selected in the southern Iberian Peninsula, these growing in similar climates but different soil types, namely a brown well-developed soil on slate rock, and a stressful lithosol on gypsum rock. In both localities, growth and maintenance respiration were measured in undetached young and mature leaves (trees under natural conditions) and fine roots (hydroponically grown seedling). Results Young leaves of the two populations displayed an almost identical growth cost (1.53 g glucose g -1 ). The maintenance cost was higher in the young (40.2 vs. 25.3 mg glucose g -1 day -1 ; P<0.05) and in the mature (7.64 vs. 4.33 mg glucose g -1 day -1 ; P<0.001) leaves of individuals growing in gypsum soils. The growth cost of fine roots was the same in both populations (1.18 g glucose g -1 ) while the maintenance cost was higher in the Gypsum population (8.95 vs. 7.39 mg glucose g -1 day -1 ; P<0.01). Conclusions The results show for first time that the cost of organ maintenance may be related to the degree of soil stress in their native habitats.
Keywords: ecotypes; evergreen leaves; growth respiration; maintenance respiration; mediterranean species; root respiration; sclerophylly; soil stress

The cost of stress resistance: construction and maintenance costs of leaves and roots in two populations of Quercus ilex - Laureano, Raquel G; Lazo, Yalín O; Linares, Juan C; Luque, Alfredo; Martínez, Feliciano; Seco, José I; Merino, José (Tree Physiology, 2008)
We tested whether growth and maintenance costs of plant organs vary with environmental stress. Quercus ilex L. seedlings from acorns collected from natural populations in the northern Iberian Peninsula and in a lower elevation and putatively less stressful habitat in the southern Iberian Peninsula were grown in pots under the same conditions. Growth and maintenance respiration were measured by CO2 exchange. Young leaves from 5-month-old seedlings of both populations had similar mean specific leaf areas, nitrogen and carbon concentrations and specific growth rates, and almost identical growth costs (1.26 g glucose g−1). Leaf maintenance cost was higher in northern than in the southern population (27.3 versus 22.4 mg glucose g−1 day−1, P < 0.01). In both populations, leaf maintenance cost decreased by 90% as leaves aged, but even in mature leaves, the maintenance cost was higher in the northern population than in the southern population (3.38 versus 2.53 mg glucose g−1 day−1, P < 0.01). The growth costs of fine roots < 1 mm in diameter were similar in the two populations (1.20 g glucose g−1), whereas fine root maintenance cost was higher in the northern population than in the southern population (9.86 versus 7.45 mg glucose g−1 day−1; P < 0.05). The results suggest that the cost of organ maintenance is related to the severity of environmental stress in the native habitat. Because the observed differences in both leaves and roots were constitutive, the two populations may be considered ecotypes.
10.1093/treephys/28.11.1721
Keywords: evergreen leaves; growth respiration; maintenance respiration; mediterranean species; respiration–nitrogen re- lationships; root respiration; sclerophylly

Adaptive strategy at the leaf level of Arbutus unedo L. to cope with Mediterranean climate - Gratani, Loretta; Ghia, Emanuela (Flora-Morphology, Distribution, Functional Ecology of …, 2002)
The adaptive strategy of Arbutus unedo L. under Mediterranean climate seemed to be due to the high leaf area (LA = 11.1 ± 0.1 cm2 ) increasing the potential capacity of light interception, the high leaf lamina thickness (L = 395 ± 10 µm) increasing the potential capacity for gas exchange, and the steeper leaf inclination at midday (α up to 63.9 ± 0.3°) determining 48% of reduction of incident radiation on a sloping leaf surface (RI), which could be a prevention mechanism against the potential photoinhibition of water-stressed leaves during drought. Nevertheless, during the drought period the photosynthetic activity and the water use efficiency (WUE) of A. unedo were strongly reduced (≥ than 50% of the maximum). Principal component analysis (PCA) underlined the higher similarity of A. unedo and Quercus ilex L. from a physiological point of view (photosynthetic rates PN , transpiration rates E, stomatal conductance gs , sub-stomatal CO2 concentration Ci ) and for leaf inclination, and with Cistus incanus L. from a phenological (leaf-life span) and structural point of view (specific leaf area SLA and leaf tissue density LTD), for leaf temperature (Tl ) and for leaf water status (leaf water potential at midday Ψmin and relative water content RWC). Therefore A. unedo might be considered in the borderline between drought semi-deciduous species and evergreen sclerophyllous species.
Keywords: Gas exchange; leaf area; leaf inclination; leaf lamina thickness; leaf-life span; sclerophylly

Adaptive strategy at the leaf level of Arbutus unedo L. to cope with Mediterranean climate - Gratani, Loretta; Ghia, Emanuela (Flora-Morphology, Distribution, Functional Ecology of …, 2002)
The adaptive strategy of Arbutus unedo L. under Mediterranean climate seemed to be due to the high leaf area (LA = 11.1 ± 0.1 cm2 ) increasing the potential capacity of light interception, the high leaf lamina thickness (L = 395 ± 10 µm) increasing the potential capacity for gas exchange, and the steeper leaf inclination at midday (α up to 63.9 ± 0.3°) determining 48% of reduction of incident radiation on a sloping leaf surface (RI), which could be a prevention mechanism against the potential photoinhibition of water-stressed leaves during drought. Nevertheless, during the drought period the photosynthetic activity and the water use efficiency (WUE) of A. unedo were strongly reduced (≥ than 50% of the maximum). Principal component analysis (PCA) underlined the higher similarity of A. unedo and Quercus ilex L. from a physiological point of view (photosynthetic rates PN , transpiration rates E, stomatal conductance gs , sub-stomatal CO2 concentration Ci ) and for leaf inclination, and with Cistus incanus L. from a phenological (leaf-life span) and structural point of view (specific leaf area SLA and leaf tissue density LTD), for leaf temperature (Tl ) and for leaf water status (leaf water potential at midday Ψmin and relative water content RWC). Therefore A. unedo might be considered in the borderline between drought semi-deciduous species and evergreen sclerophyllous species.
Keywords: Gas exchange; leaf area; leaf inclination; leaf lamina thickness; leaf-life span; sclerophylly

Leaf morphology and macronutrients in broadleaved trees in central Italy - Bussotti, Filippo; Borghini, Francesca; Celesti, Carlo; Leonzio, Claudio; Bruschi, Piero (Trees, 2000)
As part of an intensive monitoring programme (MON.I.TO, Intensive Monitoring of Forests in Tuscany), a 3-year survey was carried out, which included three tree species (beech, Fagus sylvatica L.; Turkey oak, Quercus cerris L.; holm-oak, Quercus ilex L.) located at six different sites. Leaves were sampled annually and analysed for nutrient concentrations (nitrogen, sulphur, phosphorus, magnesium, calcium, potassium and sodium) and morphological parameters (leaf area, dry weight, leaf mass per area, leaf thickness and leaf density). Results indicated considerable interannual variation of all the parameters. Differences between sampling sites indicated that, of all parameters measured, leaf mass per area could explain best the differences in field performance under conditions of stress. In fact, leaf mass per area was greater in the drier sites or when sea salt deposition occurred. Nevertheless, the variation of leaf mass per area over the 3 years did not reflect the differences in rainfall. Higher leaf mass per area was accompanied by lower concentrations of phosphorus and nitrogen, which could be a dilution effect due to an increase of structural carbon compounds in sclerophyllous leaves, as revealed by the total foliar content of these elements. Leaf mass per area as a measure of sclerophylly reached very high values among mesophile vegetation. Long-range transport of sea salt from coastal areas to mountain areas was mirrored in sodium concentrations of leaves.
Keywords: Fagus sylvatica; macronutrients; Quercus cerris; Quercus ilex; sclerophylly

Leaf morphology and macronutrients in broadleaved trees in central Italy - Bussotti, Filippo; Borghini, Francesca; Celesti, Carlo; Leonzio, Claudio; Bruschi, Piero (Trees, 2000)
As part of an intensive monitoring programme (MON.I.TO, Intensive Monitoring of Forests in Tuscany), a 3-year survey was carried out, which included three tree species (beech, Fagus sylvatica L.; Turkey oak, Quercus cerris L.; holm-oak, Quercus ilex L.) located at six different sites. Leaves were sampled annually and analysed for nutrient concentrations (nitrogen, sulphur, phosphorus, magnesium, calcium, potassium and sodium) and morphological parameters (leaf area, dry weight, leaf mass per area, leaf thickness and leaf density). Results indicated considerable interannual variation of all the parameters. Differences between sampling sites indicated that, of all parameters measured, leaf mass per area could explain best the differences in field performance under conditions of stress. In fact, leaf mass per area was greater in the drier sites or when sea salt deposition occurred. Nevertheless, the variation of leaf mass per area over the 3 years did not reflect the differences in rainfall. Higher leaf mass per area was accompanied by lower concentrations of phosphorus and nitrogen, which could be a dilution effect due to an increase of structural carbon compounds in sclerophyllous leaves, as revealed by the total foliar content of these elements. Leaf mass per area as a measure of sclerophylly reached very high values among mesophile vegetation. Long-range transport of sea salt from coastal areas to mountain areas was mirrored in sodium concentrations of leaves.
Keywords: Fagus sylvatica; macronutrients; Quercus cerris; Quercus ilex; sclerophylly

Sclerophylly and Plant Water Relations in Three Mediterranean Quercus Species - Salleo, S; GULLO, M A L O (Annals of Botany, 1990)
The possible role in drought resistance played by sclerophylly was studied in the Mediterranean oaks Quercus ilex, Q. suber and Q. pubescens. Studies were conducted on leaves at 30, 50 and 80% of their final surface area, as well as on mature leaves of the current year's growth in June and September and on 1-year-old leaves.Leaves of different ages of the three species showed quite different degrees of sclerophylly (DS). Q. ilex leaves reached the definitive DS of 1.75 g dm−2 during leaf expansion; Q. pubescens leaves hardened at the end of their expansion, with a final DS of 0.93 g dm−2; Q. suber showed the lowest DS of 0.76 g dm−2.Leaf conductance to water vapour (g1) of 1-year-old leaves of Q. ilex, measured in the field, showed a duration of the g1 peak values about twice that of the other two species. The minimum leaf relative water content (RWC), however, was near the same in the three species, indicating that water loss was recovered partly by Q. ilex leaves. This was apparently due to the higher bulk modulus of elasticity (max) as resulting from leaf water potential isotherms.High correlation coefficients were noted between DS and max but large changes in DS were needed to display minor changes in max. When both DS and max were correlated to the minimum RWC, an increase in DS of 133 % (corresponding to an increase in max of only 12 %) was needed to cause an increase in RWC of 2%. Therefore, sclerophylly cannot be considered as significantly related to a drought-avoiding strategy.
Keywords: Drought resistance; leaf conductance; Quercus ilex; Quercus pubescens (PG); Quercus suber L.; Relative water content; sclerophylly